Expression, Purification, and Functional Characterization of Atypical Xenocin, Its Immunity Protein, and Their Domains from Xenorhabdus nematophila. (18th December 2013) - Rathore, Jitendra Singh
Abstract : Xenorhabdus nematophila, a gram-negative bacterium belonging to the family Enterobacteriaceae is a natural symbiont of a soil nematode from the family Steinernematidae. In this study cloning, expression, and purification of broad range iron regulated multidomain bacteriocin called xenocin from X. nematophila (66 kDa, encoded by xcinA gene) and its multidomain immunity protein (42 kDa, encoded by ximB gene) have been done. xcinA-ximB (N′ terminal 270 bp), translocation, and translocation-receptor domain of xcinA, ximB, and its hemolysin domain were cloned, expressed, and purified by single step Ni-NTA chromatography under native conditions. In the functional characterization, neutralization of xcinA toxicity by immunity domain of ximB gene was determined by endogenous assay. Exogenous toxic assays results showed that only the purified recombinant xenocin-immunity domain (10 kDa) protein complex had toxic activity. Atypical cognate immunity protein (42 kDa) of xenocin was fusion of immunity domain (10 kDa) and hemolysin domain (32 kDa). In silico analysis of immunity protein revealed its similarity with hemolysin and purine NTPase like proteins. Hemolytic activity was not observed in immunity protein or in its various domains; however, full-length immunity protein lacking Walker motif showed ATPase activity. Finally, using circular dichroism performed secondary structural analyses of all the recombinant proteins/protein complexes.